2014
DOI: 10.1016/j.paid.2014.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Associations between schizotypy and belief in conspiracist ideation

Abstract: a b s t r a c tPrevious studies have reported associations between conspiracist ideation and domain-level facets of schizotypy, but less is known about associations with lower-order facets. In the present study, 447 adults completed measures of conspiracist ideation and the Schizotypal Personality Questionnaire (SPQ), consisting of nine subscales grouped into four domains. Results of a multiple regression showed that two domains of the SPQ significantly predicted conspiracist ideation, but multicollinearity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
122
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(140 citation statements)
references
References 18 publications
11
122
2
5
Order By: Relevance
“…Our results showed that belief in conspiracy theories was most strongly associated with the Unusual Beliefs and Experiences facet of the PID-5. In broad outline, this finding is consistent with previous work showing that facets of schizotypy closely associated with odd beliefs and magical thinking are most strongly predictive of belief in conspiracy theories (Barron et al, 2014). While it is clear that there is some shared space occupied by facets of the PID-5 and measures of schizotypy (Ashton, Lee, de Vries, Hendrickse, & Born, 2012), we believe our findings point to a broader picture of maladaptive personality traits that influence anomalous beliefs, including belief in conspiracy theories.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results showed that belief in conspiracy theories was most strongly associated with the Unusual Beliefs and Experiences facet of the PID-5. In broad outline, this finding is consistent with previous work showing that facets of schizotypy closely associated with odd beliefs and magical thinking are most strongly predictive of belief in conspiracy theories (Barron et al, 2014). While it is clear that there is some shared space occupied by facets of the PID-5 and measures of schizotypy (Ashton, Lee, de Vries, Hendrickse, & Born, 2012), we believe our findings point to a broader picture of maladaptive personality traits that influence anomalous beliefs, including belief in conspiracy theories.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we found that the facet of Suspiciousness emerged as a significant predictor of belief in conspiracy theories, although it explained only a small proportion of shared variance. In previous work, however, Barron et al (2014) reported that a schizotypy-based measure of Paranoid Ideation/Suspiciousness did not predict belief in conspiracy theories once the effects of odd beliefs had been accounted for. It would seem, therefore, that suspiciousness is only weakly associated with belief in conspiracy theories.…”
Section: Conspiracy Theories 11mentioning
confidence: 83%
See 2 more Smart Citations
“…Numerous personality factors, emotional states and social political attitudes have been found to correlate with support for CTs, including anomia (broadly: distrust towards authorities, feelings of powerlessness, and feelings of dissatisfaction about one's life; [19][20][21][22][23][24][25][26][27][28], personal and social (i.e., feeling of insecurity) anxiety [29][30][31], negative self-esteem [19,22,26,32], paranoia and schizotypy [16,21,26,28,[33][34][35][36][37], Right-Wing Authoritarianism [19,28,32,38]; but only marginally in [39], and irrationality or paranormal beliefs [16,21,24,26,28,30,35,[40][41][42][43][44]. Motivational processes have also been underlined.…”
Section: Conspiracy Theories (Cts) In Psychologymentioning
confidence: 99%